Concepts, Methods and Implementation of Education from an Islamic Character Education Perspective - Aldira Salsabilla; Ibnu Al-Kautsar Harahap; Siti Mahmudah Noorhayati; Yahanan (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
Character education has been regarded as a fundamental dimension of Islamic education aimed at developing individuals who are faithful, knowledgeable, and possess noble character. This article examined the philosophy of Islamic character education as a conceptual and normative foundation for shaping students’ personalities. The study employed a qualitative approach using a library research method by analyzing primary sources such as the Qur’an and Hadith, as well as secondary sources including the works of prominent Islamic education scholars such as Al-Ghazali, Ibn Miskawayh, and Muhammad Omar al-Syaibani. The findings show that the philosophy of Islamic character education is rooted in the principles of tawhid, human fitrah, and divine revelation as the core foundations of educational practice. Character formation is implemented through role modeling, habituation, moral instruction, motivation and deterrence (targhib–tarhib), and storytelling methods. Furthermore, the study highlights that effective implementation of Islamic character education requires strong synergy among families, educational institutions, communities, and the state. Therefore, the philosophy of Islamic character education serves as a strategic framework for fostering a generation that maintains a balance between intellectual competence, spiritual maturity, and moral excellence.